The emergence and development of Karakalpak children's folklore - Berdimuratov Jetkerbay Abatbaevich (International Journal Of Literature And Languages, 2025)
This article describes the origins, development and peculiarities of children's folklore.The importance of the ancient children's songs in the folklore of Karaqalpaq children is discussed. The peculiarities of these genres in children's folklore are highlighted, the educational importance in the folk language is highlighted, and information about the emergence of children's folklore of Karaqalpaq is given.